2008
DOI: 10.2193/2006-452
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Bear Deterrent Spray in Alaska

Abstract: We present a comprehensive look at a sample of bear spray incidents that occurred in Alaska, USA, from 1985 to 2006. We analyzed 83 bear spray incidents involving brown bears (Ursus arctos; 61 cases, 74%), black bears (Ursus americanus; 20 cases, 24%), and polar bears (Ursus maritimus; 2 cases, 2%). Of the 72 cases where persons sprayed bears to defend themselves, 50 (69%) involved brown bears, 20 (28%) black bears, and 2 (3%) polar bears. Red pepper spray stopped bears' undesirable behavior 92% of the time wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 7 publications
4
42
1
Order By: Relevance
“…Example failure Smith (1998) warned against the use of chemical sprays as some form of topical deterrent to areas or objects, as bears he observed were actually attracted to the scent and displayed vigorous rubbing and body rolling in affected areas (see also Smith et al 2008). The same could also be true for some other potential irritants, such as citronella.…”
Section: Example Successmentioning
confidence: 99%
See 4 more Smart Citations
“…Example failure Smith (1998) warned against the use of chemical sprays as some form of topical deterrent to areas or objects, as bears he observed were actually attracted to the scent and displayed vigorous rubbing and body rolling in affected areas (see also Smith et al 2008). The same could also be true for some other potential irritants, such as citronella.…”
Section: Example Successmentioning
confidence: 99%
“…Rogers (1984) found that sprayed bears never acted aggressively, and when sprayed, usually immediately retreated a short distance, where they then rubbed their eyes with their paws. Smith et al (2008) amassed all available (83) records on the use of capsaicin spray (commonly referred to as bear spray) against bears in Alaska, USA. They found that in all cases (72 of 83) where bear spray was used defensively by a person, neither bears nor people were severely injured (i.e.…”
Section: Background/overviewmentioning
confidence: 99%
See 3 more Smart Citations